Analysis of Off Highway Truck Caterpillar 773E General Overhaul (GOH) Interval - Ruspinuji, Muhammad; Kurniati, Nani (Institut Teknologi Sepuluh Nopember, 2019)
PT XYZ is a heavy equipment rental company and mining contractor. One of its working areas is an open coal mine in South Kalimantan, obtained a contract to lease heavy equipment in the form of 14 (fourteen) Caterpillar 773E Off Highway Trucks. Mine owner have availability targets and application of penalties, PT XYZ must implement appropriate maintenance and maintenance strategies. In 2018, the OHT total down time is 34,061.30 hours. For 15,272.00 hours (44.8%) downtime is caused by major component breakdown. The high cost of repairing components makes it difficult for company management to determine the decision to repair. To meet the heavy equipment availability target of mine owner, PT XYZ must implement appropriate maintenance and maintenance strategies. High off Highway Truck (OHT) availability can be achieved by minimizing downtime. The purpose of this research is to determine a general overhaul (GOH) time interval that has the greatest effect on the availability of Caterpillar 773E Off Highway Truck. In order for minimization of downtime to have a significant impact, it must be determined which critical components have the most influence on costs. Next step is determined the GOH interval by considering the smallest cost impact. The results of research show Caterpillar 773E OHT critical components are engine, transmission, final drive and torque converter. The GOH interval is 17,992.81 hours